ln(x+6)=ln(8x-5)

Simple and best practice solution for ln(x+6)=ln(8x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x+6)=ln(8x-5) equation:


Simplifying
ln(x + 6) = ln(8x + -5)

Reorder the terms:
ln(6 + x) = ln(8x + -5)
(6 * ln + x * ln) = ln(8x + -5)
(6ln + lnx) = ln(8x + -5)

Reorder the terms:
6ln + lnx = ln(-5 + 8x)
6ln + lnx = (-5 * ln + 8x * ln)
6ln + lnx = (-5ln + 8lnx)

Solving
6ln + lnx = -5ln + 8lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '5ln' to each side of the equation.
6ln + 5ln + lnx = -5ln + 5ln + 8lnx

Combine like terms: 6ln + 5ln = 11ln
11ln + lnx = -5ln + 5ln + 8lnx

Combine like terms: -5ln + 5ln = 0
11ln + lnx = 0 + 8lnx
11ln + lnx = 8lnx

Add '-8lnx' to each side of the equation.
11ln + lnx + -8lnx = 8lnx + -8lnx

Combine like terms: lnx + -8lnx = -7lnx
11ln + -7lnx = 8lnx + -8lnx

Combine like terms: 8lnx + -8lnx = 0
11ln + -7lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(11 + -7x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(11 + -7x)' equal to zero and attempt to solve: Simplifying 11 + -7x = 0 Solving 11 + -7x = 0 Move all terms containing l to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -7x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -7x = 0 + -11 -7x = 0 + -11 Combine like terms: 0 + -11 = -11 -7x = -11 Add '7x' to each side of the equation. -7x + 7x = -11 + 7x Combine like terms: -7x + 7x = 0 0 = -11 + 7x Simplifying 0 = -11 + 7x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 20x+5=5y | | (t-7)2=(t+7)2+168 | | -2(7+-2y)+3y=14 | | y^2-y+4=0 | | 4k^2-5=207 | | 8x-3x+2-x=x+x | | 13.4x=2.6x | | .5x=9-.5x | | 7x-19=-23+6x | | 15s^2-24s=63 | | y-5=7x | | 3r-7=-1+r | | 167=6+7(2+7r) | | (2x-3)(3x-4)-(x-13)(x-4)=40 | | y^2-y=28 | | 12=512+4 | | b^2-3b=88 | | x+5(5+2)+x-3(4+9)= | | 11x+35+90=90 | | 2x^2-8x+16=10 | | 11x+35+90=180 | | (5x+4)(x+3)=0 | | .75x+.05(18-x)=.10(-117) | | 49b^2-5=-1 | | (r-2)(r+7)=9 | | -20t+10=6 | | 18h^2+33h=-5 | | 49b^2-5=41 | | 63=2n+9 | | -0.3q=9 | | U=5(9n+30)+9(n+1) | | 2-7(d-1)=3(d-2)-5(f+3) |

Equations solver categories